Effect of Drying and Wetting Cycles on Deformation Characteristics of Compacted Loess and Constitutive Model - Pengju Qin; Yuqi Liu; Chungang Yang; Qingchen Yan; Yubo Liu; Li Gong; Xingji Zhu (Buildings)
Owing to the alternating processes of rainfall and evaporation, the compacted loess employed in ground and roadbed construction frequently experiences drying and wetting (D-W) cycles. These cycles are prone to induce substantial deformation of the soil mass, posing a risk to the integrity of buildings and infrastructure. Consequently, this study delved into the effects of D-W cycles on the deformation behavior of compacted loess, considering varying initial dry densities and water contents. To achieve a profound understanding of the deformation characteristics of the compacted loess, we meticulously monitored the resistivity ratio, crack ratio, and microstructure throughout the tests. Furthermore, a constitutive model was developed to forecast the deformation of compacted loess under D-W cycles. The findings revealed that both the vertical strain and crack ratio exhibited an upward trend with the increase in D-W cycle numbers, while they exhibited a downward trend as dry density increased. Notably, water content was identified as a significant factor affecting both the crack ratio and resistivity ratio. Additionally, the occurrence and progression of D-W cycles and cracks led to a slight increase in particle abundance and the proportion of total pore area. Meanwhile, during the wetting process, the infiltration of water softened the cementing substances, resulting in a disruption of the connections between aggregates. This made it much easier for cracks in the soil to expand after the sample dried. The constitutive model was meticulously constructed by incorporating yield surfaces that account for decreasing and increasing water contents. The validity of the proposed model was substantiated through a comparative analysis of the measured and calculated data. This comprehensive investigation furnishes a theoretical foundation for assessing the stability of compacted loess ground and roadbeds subjected to D-W cycles.